MEMS based Wearable Smart-Glove and its Application of Gesture Detection and Sign Language Classification for Vocally Impaired with Integrated Health Monitoring System - H., Rekha; Saisandeep, Banda; M. , Rashma; Murthy, G. N. Keshava; Tiwari, Kamalika; Datta, Subhasis (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Interactions between individuals with speech difficulties and those without have always posed challenges in communication. Gestures and sign language are recognized as the most natural and expressive means of communication between individuals with speech difficulties and those without. Through the utilization of glove-based communication systems designed for the hearing impaired, this intelligent glove enables individuals with vocal disabilities to engage in communication with others by using their sign language. Each glove is equipped with an embedded signal. The gesture module adapts the resistance of the flex sensor and accelerometer to correspond to specific gestures. Additionally, the design includes a text-to-speech converter that transforms intended actions into spoken output, which is then emitted through a speaker or transmitted via Bluetooth to a connected phone. This prototype also incorporates automatic message alerts for relevant parties, along with health monitoring capabilities for detecting human body temperature and heart rate. Overall, the health monitoring system is a valuable addition to the smart glove-based communication device, and it further enhances its potential to improve the lives of individuals with speech impairments.